Korelasi antara skor Child-Pugh dengan gastropati hipertensi portal pada penderita sirosis hati - Faisal Parlindungan; Mabel Sihombing (Fakultas Kedokteran USU, 2013)
Introduction : Hypertensive portal gastropathy (PHG) is a pathologic appearance on the gastric mucosa which can cause acute or chronic bleeding in liver cirrhotic patients. The pathogenesis of PHG is controversial and there is no agreement on the effect of liver dysfunction to PHG. This study aims to evaluate correlation between liver dysfunction severity that is assessed by Child-Pugh score and PHG in liver cirrhotic patients.Methods : This is an analytic cross sectional study. The demographics and clinical data were recorded, laboratory tests were performed (albumin, INR and bilirubin) to calculate Child-Pugh score, and patients underwent esophagogastroduodenoscopy (EGD) to assess PHG. Correlation between Child-Pugh score and PHG were tested with Spearman correlation analysis. Cut-off value of Child-Pugh score was determined with receiver operating characteristics (ROC) analysis which is followed by diagnostic performance analysis.Results : From 41 subjects, there were 8, 18, 15 patients with Child-Pugh class A,B, and C respectively. On endoscopic examination, there were 10,19, and 12 patients without PHG, with mild PHG, and with severe PHG respectively. There is a positive correlation between Child-Pugh score and the severity of PHG (r = 0.556; P = 0.0001). Among Child-Pugh score components, ascites and bilirubin showed positive correlation with PHG. Using cut off point of • 7, Child Pugh score showed 87.1% sensitivity, 40% specificity, 81.8% PPV, 50% NPV, 1.45 LR(+), 0.32 LR(-), accuracy diagnostic was 75.6% and the AUROC was 0.65 (95% CI:0.437-0.860; P = 0.163)Conclusion: Child-Pugh score has a positive correlation with severity of PHG, in which higher Child-Pugh score is correlated with more severe PHG.Keywords : Child-Pugh Score; portal hypertensive gastropathy; liver cirrhotic; endoscopy